Dietary Magnesium Intake Ameliorates the Association Between Household Pesticide Exposure and Type 2 Diabetes: Data From NHANES, 2007–2018 - Huang, Jungao; Hu, Liqin; Yang, Juan (Frontiers in Nutrition, 2022)
Aims/hypothesis This study aimed to explore whether household pesticide exposure in the general population increased the risk of developing type 2 diabetes and whether intake of dietary magnesium could lower type 2 diabetes from household pesticide exposure. Methods For this cross-sectional study, we obtained the data of 9187 United States adults from the National Health and Nutrition Examination Surveys, 2007–2018. Participants were subdivided into two groups based on the amount of daily dietary magnesium in the population: low group: <175 mg/day and high group: ≥175 mg/day. Using multivariable logistic regression analysis, we evaluated the relationship between pesticide exposure in the home and type 2 diabetes. Results Compared to those unexposed at home, individuals who were exposed to pesticides in their households had a relatively higher odds ratio for type 2 diabetes (OR=1.22, 95% CI: 1.04-1.44). The association of pesticide exposure in the home with the incidence of type 2 diabetes was different for low and high dietary magnesium groups, OR=1.66, 95% Cl: 1.19-2.33 vs. OR=1.1, 95% Cl: 0.92-1.32, respectively. An interaction (P=0.035) between household pesticide exposure and magnesium intake, suggested that high dietary magnesium intake may reduce the risk of developing type 2 diabetes from pesticide exposure. Conclusions Household pesticide exposure in the general population is associated with an elevated risk of type 2 diabetes. We report for the first time possible clinical relevance in that high magnesium intake may ameliorate the increased risk of type 2 diabetes from pesticide exposure.